2013
DOI: 10.4103/1463-1741.113523
|View full text |Cite
|
Sign up to set email alerts
|

Personal listening devices and the prevention of noise induced hearing loss in children: The cheers for ears pilot program

Abstract: To determine whether the Cheers for Ears Program on noise induced hearing loss prevention was effective in improving current knowledge of noise impact of personal listening devices on hearing, and in changing self-reported listening behavior of primary school students aged between 9 years and 13 years. A survey study was implemented at participating primary schools. Schools represented various levels of socio-economic status. Informed consent (parents and teachers) and informed assent (pupils) were obtained. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 23 publications
1
30
0
6
Order By: Relevance
“…The authors believe that the repetition of prevention campaigns for adolescents will establish appropriate attitudes regarding noise exposure. Another study (6) developed a pilot programCheers for Ears -which was able to improve the knowledge of pre-adolescents about the impact of noise on hearing and the habits of primary school students. The program included multimodal educational and interactive activities appropriate for the students' age, as well as a long-term questionnaire evaluation in which it was observed that the changes related to the knowledge of hearing and the habit of the students regarding noise exposure were stable and sustained for up to 3 months after the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors believe that the repetition of prevention campaigns for adolescents will establish appropriate attitudes regarding noise exposure. Another study (6) developed a pilot programCheers for Ears -which was able to improve the knowledge of pre-adolescents about the impact of noise on hearing and the habits of primary school students. The program included multimodal educational and interactive activities appropriate for the students' age, as well as a long-term questionnaire evaluation in which it was observed that the changes related to the knowledge of hearing and the habit of the students regarding noise exposure were stable and sustained for up to 3 months after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers worried about the exposure of youths to noises harmful to the hearing have developed different educational programs for implementation in school classrooms aiming at increasing knowledge about the damages caused by excessive exposure to noise and need of use of hearing protectors. The effectiveness of these programs has been demonstrated in questionnaires applied before and after the interventions, showing changes in the behavior and attitudes of adolescents regarding hearing habits (3,4,5,6,7) . In this context, the earlier the child becomes aware of hearing risks caused by loud noise through educational campaigns and programs implemented in primary schools, more effective their knowledge, attitudes, and intentions will be regarding the prevention of hearing loss once they become adolescents, thus avoiding common risk behaviors (5,14,15) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to high-level sound and hearing loss, personal experience of noise injury symptoms, appreciation of long-term implications of hearing damage, affinity for music, awareness of the benefits of earplugs, and high self-efficacy appear to be key variables (Beach et al, 2012). Interactive, age-appropriate programs, which include a variety of activities, have a greater chance of success with respect to both learning and behavioral change, and the basis for the activities should include education on how hearing loss may affect individuals' lives and what activities are potentially dangerous to hearing (Folmer et al, 2002;Henderson, Testa, & Hartnick, 2011;Taljaard, Leishman, & Eikelboom, 2013).…”
mentioning
confidence: 98%
“…This commercially available training program is intended to encourage use of hearing protection devices (HPDs) by young musicians via a structured educational program provided when a band is adopted. This training incorporates many aspects of other hearing loss prevention educational programs for adolescents or young adults, such as the Dangerous Decibels program (Griest et al, 2007;Martin et al, 2013), Sound Sense (Neufeld et al, 2011), and the Cheers for Ears program (Taljaard et al, 2013). The Adopt-a-Band adoption kit includes information about how the ear works, how loud sounds (specifically including music) affect hearing, what changes in hearing can occur with exposure to loud sound, and information about what can be done to protect one's own hearing.…”
mentioning
confidence: 99%